2014
DOI: 10.1007/s11748-014-0372-3
|View full text |Cite
|
Sign up to set email alerts
|

A case of thoracic esophageal cancer with an unusual type of duplicated inferior vena cava

Abstract: We describe here a thoracic esophageal cancer with an unusual type of duplicated inferior vena cava. A 58-year-old man was referred to our hospital because a tumor in his lower esophagus had been identified by endoscopy and radiology. Computed tomography scans showed an unusual type of duplicated inferior vena cava characterized by both common iliac veins flowing back into the left-sided inferior vena cava, which drained into the azygos vein, whereas the right-sided one had no drainage. Esophagectomy was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Considering the unremarkable physical examination and laboratory test results of patients with such an anomaly, recognition of the warning signs (enlarged azygos vein and arch of the azygos vein) of this anomaly as visualized on preoperative CT and during intraoperative exploration is vital. To date, there have been only six reported cases of azygos continuation of the IVC in patients undergoing esophagectomy ( 2 4 , 6 ) ( Table 1 ). Three patients were safely discharged with adequate arch of azygos vein protection ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the unremarkable physical examination and laboratory test results of patients with such an anomaly, recognition of the warning signs (enlarged azygos vein and arch of the azygos vein) of this anomaly as visualized on preoperative CT and during intraoperative exploration is vital. To date, there have been only six reported cases of azygos continuation of the IVC in patients undergoing esophagectomy ( 2 4 , 6 ) ( Table 1 ). Three patients were safely discharged with adequate arch of azygos vein protection ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shintakuya et al [ 3 ] have reported one case in which oesophagectomy was performed on a patient with a duplicated IVC, and azygos vein variation was identified by preoperative CT. Therefore, during oesophageal carcinoma surgery for patients with azygos vein variation, it is extremely important to maintain the integrity of the azygos vein.…”
Section: Discussionmentioning
confidence: 99%